Macrocycle‐Based Covalent Organic Frameworks. Issue 16 (23rd February 2023) - Yuan, Yufei; Bang, Ki‐Taek; Wang, Rui; Kim, Yoonseob
Abstract: Macrocycles with well‐defined cavities and the ability to undergo supramolecular interactions are classical materials that have played an essential role in materials science. However, one of the most substantial barriers limiting the utilization of macrocycles is their aggregation, which blocks the active regions. Among many attempted strategies to prevent such aggregation, installing macrocycles into covalent organic frameworks (COFs), which are porous and stable reticular networks, has emerged as an ideal solution. The resulting macrocycle‐based COFs (M‐COFs) preserve the macrocycles' unique activities, enabling applications in various fields such as single‐atom catalysis, adsorption/separation, optoelectronics, phototherapy, and structural design of forming single‐layered or mechanically interlocked COFs. The resulting properties are unmatchable by any combination of macrocycles with other substrates, opening a new chapter in advanced materials. This review focuses on the latest progress in the concepts, synthesis, properties, and applications of M‐COFs, and presents an in‐depth outlook on the challenges and opportunities in this emerging field. Abstract : Macrocycles such as porphyrins, phthalocyanines, corroles, benzoannulenes, crown ethers, cyclodextrins, cucurbiturils, calixarenes, or pillararenes can be installed on covalent organic frameworks to make macrocycle‐based covalent organic frameworks for applications such as single‐atom catalyst, adsorption, electronics, photodynamic therapy, and single‐layer design.